Peculiarities of movement of geostationary satellites - Demchenko, B.I.; Komarov, A.A.; Serebryanskiy, A.V.; Usoltseva, L.A.; Akniyazov, Ch.B. (Recent Contributions to Physics, 2017)
The definition of an ideal geostationary satellite (GSS) is given. It is practically impossible to deduce a GSS strictly on an ideal orbit. The difference between the real GSS and the ideal is shown. The problem of GSS cataloging is discussed. As the launch of new objects or correction of orbits of already existing satellites, the current directory has to be constantly supplemented and updated. A simplified theory of the longitude change of the GSS with time is given, taking into account the second sectorial harmonic in the expansion of the geopotential. On the basis of this theory, two classes of uncontrolled GSS (libration and drifting) are distinguished, and an estimate of the resonant perturbations for both classes is given. An empirical evolutionary «inclination-node» diagram for the orbital plane of the GSS for the period 1991-2016 is given.